Pre-emptive sovereign debt restructuring and holdout litigation - Kartik Anand; Prasanna Gai (Deutsche Bundesbank, 2018)
We offer an analytical framework for studying "pre-emptive" debt exchanges. Countries can tailor a sovereign bankruptcy framework by choosing provisions (or "haircuts") ex ante, but must contend with the market discipline of holdout litigation ex post. Secondary markets play a role in shaping the holdout costs facing the sovereign, and our results suggest that it is optimal to prioritise the rights of holdout creditors during litigation so that they are always paid in full. We clarify how macroeconomic and legal factors influence the choice of haircut. Our model contributes to the debate on sovereign debt restructuring by formalizing Bolton and Skeel's (2004) notion of a "Designer SDRM".
Keywords: F34; F55; G33; K4; 330; sovereign debt restructuring; holdout creditors; bankruptcy procedures; absolute priority